2019
DOI: 10.1371/journal.pbio.3000086
|View full text |Cite
|
Sign up to set email alerts
|

Astroglial dysfunctions drive aberrant synaptogenesis and social behavioral deficits in mice with neonatal exposure to lengthy general anesthesia

Abstract: Lengthy use of general anesthetics (GAs) causes neurobehavioral deficits in the developing brain, which has raised significant clinical concerns such that the United States Food and Drug Administration (FDA) is warning on the use of GAs in children younger than 3 years. However, the molecular and cellular mechanisms for GAs-induced neurotoxicity remain largely unknown. Here, we report that sevoflurane (Sevo), a commonly used GA in pediatrics, caused compromised astrocyte morphogenesis spatiotemporally correlat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 53 publications
3
61
0
Order By: Relevance
“…Both excitatory and inhibitory synaptic inputs have been shown to be regulated by sevoflurane during postnatal development. Lengthy sevoflurane exposure at P7 has been reported to compromise astrocyte development, which arrests excitatory synapse maturation and results in decreased mEPSC frequency in cortical pyramidal neurons 41 . Long-term reduction in excitatory inputs may cause homeostatic scaling of excitatory synapses a and indirectly enhance neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Both excitatory and inhibitory synaptic inputs have been shown to be regulated by sevoflurane during postnatal development. Lengthy sevoflurane exposure at P7 has been reported to compromise astrocyte development, which arrests excitatory synapse maturation and results in decreased mEPSC frequency in cortical pyramidal neurons 41 . Long-term reduction in excitatory inputs may cause homeostatic scaling of excitatory synapses a and indirectly enhance neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, any adverse external intervention factors including anesthetics can affect the development of the embryonic brain. Recently, Zhou (2019) have shown that sevoflurane drove aberrant synaptogenesis and social behavioral deficits in neonatal mice by disrupting astrocyte Ca 2+ homeostasis which induced astroglial dysfunctions. ZOā€1, also known as tight junction proteinā€1, and postsynaptic densityā€95 (PSDā€95) were important protein markers of neurogenesis and synaptogenesis in the central nervous system (Beckā€Schimmer et al, 2020; Park et al, 2015).…”
Section: Sevoflurane and Neurogenesismentioning
confidence: 99%
“…If molecular structure changes, it will have an effect on the learning and memory ability [1,2]. There are many reports stating that long-term, repeated, or high-dose sevoflurane anesthesia in neonatal rats can cause changes in nervous system function and affect the long-term learning and memory and cognitive function [3][4][5]. The FDA warned that repeated or prolonged (more than 3 h) use of anesthetics and sedatives may impair the brain of fetus and children less than 3 years [6].…”
Section: Introductionmentioning
confidence: 99%